Fertilization improves the production of natural wet grasslands in the oriental High Atlas mountains of Morocco: the case of Imilchil region - Homrani Bakali A.; Acherckouk M.; Maatougui A.; Mrabet R. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The oriental High Atlas mountains in southeast of Morocco are characterized by small areas of natural wet grasslands called Almo. These are well managed by the local population in order to feed cattle and mullets. Under the framework of a research and development project, a trial was implemented in order to assess the effects of nitrogen fertilization on the phytomass production of the natural wet grasslands of Tissila (6.5 Ha) in the Imilchil region. The experimental design consisted in dividing the grassland into three plots: a “control” plot (P1, without fertilisation) and two experimental plots which received two different doses of nitrogen split in three applications during the year. The first plot (P2) received a cumulated amount of 134 kg N/ha plus 46 Kg P2O5/ha in two applications; the second plot (P3) received a cumulated amount of 67 kg N/ha plus 46 Kg P2O5/ha, applied similarly to P2. The phytomass production doubled with fertilization, even at the lowest dose (P3). The assessment of flora revealed a great specific richness (79 species) and some endemism which should be preserved.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)